Generation Alpha’s expectations at work: Well-being, pay and sense of agency - Marzena Syper-Jędrzejak; Katarzyna Wojtaszczyk; Patrycja Mizera; Izabela Różańska-Bińczyk; Paweł Łuczak (PLoS ONE, 2026)
In contemporary organizations, representatives of different generations meet. Many publications have been written about the work style, expectations, and needs of representatives of previous generations, but we notice a certain gap concerning the youngest participants of the labor market, i.e., Generation Alpha. The aim of the publication was to find answers to the questions about the requirements for remuneration and well-being at work of young people in Poland, whether these two groups of expectations are causally related, and what is the role of the sense of agency of representatives of Generation Alpha in this causal-effect system. We surveyed 446 respondents aged 19–22, selected on a quota basis. The results of the study confirmed that the expectations of the youngest players in the labor market go in many directions: first, toward earning “good” money, secondly – well-being at work is important. We confirmed that the expectation of young people regarding satisfactory remuneration is related to the expectations (and implicitly also the search for) of an employer who will ensure well-being at work. However, it was not possible to directly confirm the mediating role of the high sense of agency in the relationship between expectations about pay and well-being at work.